OS SABERES ECOLÓGICOS TRADICIONAIS DE AGRICULTORES DA COMUNIDADE RURAL LINHA CRICIUMAL E SUA RELAÇÃO COM A PAISAGEM RURAL - CÂNDIDO DE ABREU, PR - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2014)
The ethno approach, and the main branch to ethnoecology seeks study of local knowledge about natural processes populations, trying to discover the logic behind human knowledge of the natural world. Being a focus of anthropology, considered disciplinary, encompassing methodologies and concepts from other sciences such as agronomy, biology, and in this case also the geography, the concept of landscape. The landscape, while experience and narrative, is experienced in the day-to-day life of every individual and of the community as a whole and perceived by the representations of this about that experience. The concept of landscape thus is shared also by anthropology. The relationship between landscape and ethnosciences has connection with the concept of culture implied in the ethnometodologys, that by dealing with approaches that seek to understand the knowledge of human groups can be used both by geography and anthropology. In this way, the objective was to interpret the ethnoscientific and geographical bias, traditional ecological knowledge of farmers of rural community Linha Criciumal and its relationship with the rural landscape. To achieve this objective the present study was divided in four articles, the first two being theoretical and the last two presenting results of field work: 1) State of the art in Brazilian and international ethnoscience; 2) Geographical and ethnoscientific approaches of the rural landscape: geossímbolo, representations of nature and productive practices; 3) Etno-agronômic study of practices (i) materials in the landscape of rural community Linha Criciumal, Cândido de Abreu (PR); 4) The relationship between traditional ecological knowledge and rural landscape. At first, aimed to characterize etno-agronômic practices of the local agrarian system, then investigated the relation of knowledge of farmers with the local landscape and finally sought out the correlation between local knowledge and scientific knowledge. To do so, we sought a rapprochement with the community, from etnometodologias, emphasizing the technique of oral history. Then, a pilot test was applied, seeking to validate the research and find a key informant. In the course of time the semi-structured interviews were conducted, inherent in participatory methodology with family farmers. Other techniques relating to data collection were participant observation, use of satellite imagery as diagnostic tools and landscape mapping and of the lands; opening and description of soil profiles; morphological description; guided excursions to collect indicator plants, etc. Finally sought to the correlation of the vernacular knowledge about the quality and types of lands with indicator plants and with the scientific knowledge about the quality and kinds of soils. The etno-agronômic analysis of the local agrarian system made it possible to understand that the practices (tangible and intangible) of Community Linha Criciumal are adapting to the factors of modernity, in particular the changes that occur in agriculture, so that through these practices the landscapes and the set of elements that constitute the local agrarian system, underscore a hybridity between the modern and the traditional. It was also possible, on the one hand, perform the classification of local plants and lands of the agricultural landscape of this community and, on the other hand, was investigated attributes physical, chemical and biological soil, classified by the SBCS, as well as the botanical classification of indicator plants of the quality of the lands. In this sense, it was possible to correlate the class ethnopedological Terra Branca („bad land‟) the Cambissolo Háplico Ta Eutrófico léptico and Neossolo Litólico Distrófico fragmentário and plant species like Samambaia, Guanxuma, Sapé, Erva-quente, etc. The Terra Amarela class was correlated with Cambissolo Háplico Alítico léptico and Camibissolo Háplico Alítico típico and be „bad land‟ is also associated with the same indicator species found in Terra Branca. Already the class Terra Roxa („good land‟) correlated the Neossolo Litólico Eutrófico fragmentário and Argissolo Vermelho Eutrófico nitossólico and plant species as Tomatiro/Catarinete, Mamona, Ingazeiro, Caruru-roxo, Lixeira, etc.
TRADITIONAL ECOLOGICAL KNOWLEDGE OF FARMERS IN THE RURAL COMMUNITY LINHA CRICIUMAL AND ITS RELATION TO RURAL LANDSCAPE - CÂNDIDO DE ABREU, PR
Keywords: Linha Criciumal; Conhecimento local; Paisagem rural; Hibridismo; Etnoecologia; Imaginário de fertilidade; Linha Criciumal; Local knowledge; Rural landscape; Hybridity; Ethnoecology; Imaginary of fertility; CNPQ::CIENCIAS HUMANAS::GEOGRAFIA